Theoretical behaviors of elastohydrodynamic lubrication in circular contact with newtonian fluid - Wongseedakaew, Khanittha (Engineering and Applied Science Research, 2012)
This paper presents the theoretical behaviors of isothermal elastohydrodynamic lubrication with Newto-nian fluid for a sphere on plate in circular contact. The time independent Reynolds equation, elastic equation and viscosity equation were formulated for compressible fluid. Finite Difference method, Newton-Raphson method and multigrid method were implemented to obtain the film pressure profiles and film thickness profiles in the contact region at various loads and speeds. The simulation results show that the film pressure increase but minimum film thickness decrease when the loads increase. For increasing the speeds, film thickness increases. Keywords : Reynolds equation, Elastohydrodynamic lubrication, Multigrid method, Circular contact